Analyzing biodiesel for contaminants and moisture retention. Issue 3 (May 2012) - He, B Brian; Van Gerpen, Jon H
This article reviews the contaminants that affect biodiesel fuel quality and the analytical procedures used for their determination. These contaminants include those causing cold flow problems and filter plugging, acid number and moisture. The significance and determination of the levels of the contaminants that affect low-temperature operability and cause filter-plugging problems, including mono-acylglycerides and sterol glucosides, are reviewed and discussed. Additionally, the significance and measurement of acid number and moisture content are reviewed in regard to their effects on fuel quality.